Seismic Performance Evaluation of Reinforced Concrete Moment Frames with Gravity Columns - Akbas, Bulent; Doran, Bilge; Bozer, Ali; Seker, Onur; Faytarouni, Mahmoud; Shen, Jay (ASCE-AMER SOC CIVIL ENGINEERS, 2020)
Moment frames with gravity columns in reinforced concrete (RC) buildings have been used extensively for the last decade in the United States. Unlike traditional beam-column-slab structures, they provide some advantages in terms of construction time and architectural and economical aspects in design process. The system consists of gravity-only columns resting directly on slabs and seismic force-resisting moment frames. Reinforced concrete special moment frames in two principal directions are typically placed at the perimeter as a lateral force-resisting system. Even though the design procedure is similar to that used with steel special moment frames, there is generally no column at the corner of the plan in such buildings so as to avoid biaxial bending. This paper investigates the contribution of gravity-only columns to inelastic seismic response of low- and high-rise RC special moment frames. For this purpose, nonlinear dynamic time history analyses are carried out on 5- and 15-story RC buildings designed with current design specifications subjected to design-level earthquake ground motions. Seismic performance evaluation was also carried out through nonlinear dynamic time history analyses. (c) 2020 American Society of Civil Engineers.
Keywords: Reinforced concrete moment frame design; Gravity columns; Nonlinear dynamic analysis; Plastic deformation; Failure mechanism; Strain-based performance evaluation; COLLAPSE; DESIGN; Engineering